2021
DOI: 10.1016/j.jot.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of N6-methyladenosine (m6A) modification during the degeneration of lumbar intervertebral disc in mice

Abstract: Objective To study the N6-methyladenosine (m 6 A) modification pattern of nucleus pulposus (NP) tissue during intervertebral disc degeneration (IDD). Methods A standing mouse model was generated, and staining and imaging methods were used to evaluate the IDD model. Methylated RNA immunoprecipitation with next-generation sequencing (MeRIP-seq) was used to analyze m 6 A methylation-associated transcripts in the NP, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
(65 reference statements)
2
11
0
Order By: Relevance
“…Our data indicated that m6A regulation was complex. Both hypomethylated and hypermethylated m6A could induce or reduce mRNA expression, which was consistent with previous studies 34,35 . The differentially expressed genes with altered m6A methylation included small proline-rich repeat protein 1A (sprr1a), c-type lectin domain family 4 member D (clec4d) and apelin receptor (aplnr).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicated that m6A regulation was complex. Both hypomethylated and hypermethylated m6A could induce or reduce mRNA expression, which was consistent with previous studies 34,35 . The differentially expressed genes with altered m6A methylation included small proline-rich repeat protein 1A (sprr1a), c-type lectin domain family 4 member D (clec4d) and apelin receptor (aplnr).…”
Section: Discussionsupporting
confidence: 93%
“…Both hypomethylated and hypermethylated m6A could induce or reduce mRNA expression, which was consistent with previous studies. 36,37 The differentially expressed genes with altered m6A methylation included small proline-rich repeat protein 1A (sprr1a), c-type lectin domain family 4 member D (clec4d) and apelin receptor (aplnr). Sprr1a is highly expressed in injured neurons and thought to be a regeneration-associated gene (REG) that promotes spontaneous axon growth.…”
Section: Discussionmentioning
confidence: 99%
“…NPC is exposed to various stress environments, and stress is an upstream regulatory signal of m6A in NPC. Zhu, Chen, et al (2021). established a standing mouse model to induce IDD by enhancing the mechanical compression of IVD.…”
Section: Npc Autophagy Under Stress Is Possibly Mediated By M6a Methy...mentioning
confidence: 99%
“…These regions overlapped spatially with the enhancer-binding region of the serine- and arginine-rich splicing factor (SRSF), which modulated mRNA splicing ( Zhao et al, 2014 ). It has been suggested that depletion of FTO enhanced the m6A level and promoted the affinity of SRSF2 binding with RNA, thereby increasing the number of target exons and inducing RNA maturation ( Zhu et al, 2021 ). Furthermore, the m6A reader YTHDC1 could recruit the splicing factor SRSF3 to promote exon inclusion but antagonize SRSF10 mRNA binding, which facilitated exon skipping ( Xiao et al, 2016 ).…”
Section: Crosstalk Between N6-methyladenosine Modification and Rnas I...mentioning
confidence: 99%